Between Baghdad and Birmingham: minorities - Christian and Muslim - Waardenburg, Jean Jacques (Islam and Christian-Muslim relations, 2003)
This paper deals with majority-minority relations that very much condition relations between Muslims and Christians. The first part gives some factual data about Muslim minorities in Europe and Christian minorities in Muslim countries and makes some comparisons between their situations at present. The second part questions the very idea of speaking of Muslims and Christians in terms of majority and minority, since this imposes a political scheme on human reality, neglecting existing diversities within the communities and in the relations between them. More important questions are: what have Muslims and Christians done with their religions in minority and majority situations? How can a model of participation in civil society replace the traditional Middle Eastern model of social separateness with religiously justified antagonisms? How can the positive potential of minorities be better appreciated? The author pleads for practical realism and enlightened participation instead of fixing and quantifying Muslim and Christian religious communities as closed social entities.